Freshwater use of the energy sector in Africa. (15th July 2020) - Gonzalez Sanchez, Rocio; Seliger, Roman; Fahl, Fernando; De Felice, Luca; Ouarda, Taha B.M.J.; Farinosi, Fabio
Highlights: Water use throughout the different stages of energy production in Africa is analysed. Important amounts of water are lost through evaporation in hydropower reservoirs. Fuelwood used in households is an important water consumer. The water use in thermal power plants depends highly on the type of cooling system. Non-hydro renewables are a good alternative for sustainable development in Africa. Abstract: The fast economic and population growth in the African continent will lead to an important increase in demand for energy and water resources. Unfortunately, very few studies have addressed water use for energy production in Africa. This study focuses on water consumption and withdrawals throughout the different stages of energy production (fuel production, power plant construction and operation) in African countries. An in-depth analysis of water loss through evaporation in hydropower reservoirs is also performed due to the important role it plays in many countries and its severe impacts on electricity generation during the increasingly frequent droughts in Africa. The results indicate that in the year 2016, a total of 42 billion cubic meters of water was lost through evaporation in hydropower reservoirs compared to 1.2 billion cubic meters from all the other fuel types combined. Oil extraction and refining dominate water use for fuel production and non-hydro renewable energies have an almost negligible impact on the overall water use (10 million cubic meters). Fuelwood is shown to be a high consumer of water accounting for 4.5 billion cubic meters. The use of non-hydro renewable energies instead of fossil fuels can contribute significantly to reduce water use while covering the growing energy needs in Africa. Modern technologies that substitute fuelwood use in households would also reduce the impacts on water resources. The hydropower potential remains largely untapped in several regions of the continent. Nevertheless, new hydropower developments need to be carefully considered especially in regions characterized by severe water scarcity.